Disease Burden Of Co-Occurring Borderline Personality Disorder In Patients With Bipolar Disorder - M. Turki; M. Abdellatif; N. Gargouri; S. Ellouze; S. Blanji; A. Daoud; N. Halouani; J. Aloulou (European Psychiatry, 2022)
Introduction In recent years, advances in the areas of both bipolar disorder (BD) and borderline personality disorder (BPD) have generated considerable interest in the relationship between these two conditions, since that they are commonly comorbid.